Effect of Benson’s relaxation technique on death anxiety among patients with breast cancer - Samira Moradipour (حیات, 2019)
Background & Aim: Breast cancer is one of the most prevalent cancers in women and is regarded as a chronic disease with various psychological complications including death anxiety. This study aimed to examine the effect of Benson’s relaxation technique on death anxiety among women with breast cancer. Methods & Materials: In this randomized clinical trial, 100 patients with breast cancer referred to Velayat Hospital in Qazvin in 2017 were selected using the consecutive sampling and randomly assigned into groups of experimental and control. A questionnaire on demographic information and the Templer Death Anxiety Scale were used. Benson’s relaxation technique was taught to the patients in the experimental group. Afterward, they were asked to perform the technique for three months and were monthly followed up using checklists. The Templer Death Anxiety Scale was completed again by both groups. Data were analyzed via the SPSS software version 23 using descriptive and analytical statistics. Results: There was no significant difference in demographic variables between the two groups (P>0.05). Before the intervention, no statistically significant difference was observed between the mean scores of death anxiety in the patients of the experimental group (46.4±10.3) and the control group (49.6±10.07) (P>0.05). However, after the intervention, a statistically significant difference was observed between the mean scores of death anxiety in the experimental group (44.5±10.2) and the control group (48.9±11.2) (P<0.05). Conclusion: According to the results of the study, it can be concluded that Benson’s relaxation technique is effective in reducing death anxiety among patients with breast cancer. Clinical trial registry: IRCT20170610034435N8